A Concise Total Synthesis of 2-epi-(–)-Pachastrissamine via a Three-Component Tandem Cross-Metathesis–Intramolecular SN2′ Substitution–Cross-Metathesis Sequence - Lee, Dongjoo (Synlett, 2012)
A highly concise and efficient total synthesis of 2-epi-(–)-pachastrissamine is described utilizing a three-component tandem cross-metathesis–intramolecular SN2′ substitution–cross-metathesis from the readily available alcohol (+)-8, wherein the substituted tetrahydrofuran formation and alkyl-chain extension are both accomplished in a one-pot manner. This route allows for direct access to pachastrissamines and their synthetic analogues at C(2).
Keywords: total synthesis; tandem reaction; stereoselective synthesis; natural products; 2-epi-pachastrissamine